Development of Basic English Learning Application (Easy English) - MOHD RAZALI, NUR SYAMIMI; Tassim, Siti Nabila (Research and Innovation in Technical and Vocational Education and Training, 2022)
The Malaysian government's policy is to make English as the second language after National language. However, the use of English is still not widespread among students at the primary school level. Therefore, the purpose of this study is to develop a basic learning application of English to be one of the teaching and learning materials in English. It aims to design content, design interactivity, design interfaces, develop and test the functionality of basic English learning android applications. The ADDIE model was chosen in the design model to develop this application because it is suitable for multimedia development. The model has five phases namely analysis, design, development, implementation and evaluation. The software used to develop this application is Unity and Adobe Illustrator. The research instrument used is an expert questionnaire to assess the level of functionality of the application. The development of this application was evaluated by expert respondents consisting of three expert lecturers of the Creative Multimedia program and one expert respondent from the Language Center. Data were obtained, analyzed, and presented in the form of frequency, percentage of acceptance and feedback notes. Overall, this basic English learning application was successfully developed and received positive reviews and views from all four experts.